The Importance of Financial Statements for MSMEs in South Tambun Subdistrict - Yudhi Adnan Prayogo; Murtanto Murtanto (Transpublika Publisher, 2025)
The primary objective of this paper is to enhance awareness regarding the significance and comprehension of business entities in creating financial statements for MSMEs. A quantitative descriptive research approach was employed for this investigation. Primary data was gathered through questionnaires distributed to 150 MSME participants in South Tambun District, Bekasi Regency. Data collection involved both direct interaction and secondary means through surveys. The Partial Least Square (PLS) technique was utilised for processing and analysing the data. The findings revealed that the significance of financial statements plays a crucial role in the operations of micro, small, and medium enterprises. As a result, managers should prioritise financial statements and associated risks for improved knowledge and preparedness for future challenges.